Agradecimiento: Carmen Granados, Jonathan Chaves, Javier Calvo, Ana Laura Murillo, Jeffry Ulate, Danny Arroyo, Adrián Arguedas y Ruddy Espinoza - Educare, Revista Electrónica (Revista Electrónica Educare, 2004)
Documento adjunto